A successful conservative management of cervical ectopic pregnancy - Ramanathan, Ramayee; Rajan, Niranjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Cervical ectopic pregnancy is a rare life-threatening condition with an incidence of less than 1% among all ectopic pregnancies. A 27-year-old primigravida presented with spotting per vaginum following 4 weeks 5 days of amenorrhea. Transvaginal ultrasound done at 4 weeks 5 days showed a gestational sac located in the anterior wall of cervix, diagnosis of cervical ectopic pregnancy was made. Initial serum beta hCG titre was 4106 mIU/ml. Serial monitoring of serum beta hCG done showed increasing values. Hence, decided for medical management with single dose of injection methotrexate, as the diagnosis was made at an early gestation and patient was hemodynamically stable. On follow up, serum beta hCG did not fall significantly, hence multidose methotrexate regimen was initiated. She responded to it, but she continued to have persistent bleeding per vaginum with fall in hemoglobin levels, hence sorted for surgical management which included suction and evacuation, after ligation of descending cervical artery and subsequently cervical tamponade. Intraoperative period was uneventful. On follow-up, patient was asymptomatic and vitals stable. Serum beta hCG done 2 weeks post procedure was below 5 mIU/ml and resumed spontaneous cycles after a month. Thus, early detection and accurate diagnosis of cervical ectopic pregnancy using ultrasound and serial beta hCG titre monitoring becomes a cornerstone of management. We present this case as it was her index pregnancy, with a need to preserve future fertility, successful conservative management of Cervical ectopic pregnancy with combination of medical and surgical intervention.